The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Libro De Actas IN-RED 2020: VI Congreso De Innovación Edicativa Y Docencia en Red 2020
DOI: 10.4995/inred2020.2020.11979
|View full text |Cite
|
Sign up to set email alerts
|

Estrategia tecnológica para nivelar los presaberes matemáticos en la educación superior

Abstract: Las Tecnologías de la Información y la Comunicación (TIC) permiten utilizar en el ámbito educativo espacios digitales que poseen metodologías innovadoras y creativas para potenciar el aprendizaje de los estudiantes en diferentes áreas del conocimiento. De otro lado, las altas tasas de deserción y repetición en las asignaturas del área de matemáticas en los primeros semestres académicos de la educación superior evidencian, entre otras posibles causas, el bache formativo en los presaberes matemáticos de los estu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Among the limitations of the study, it is worth noting that despite the large sample size, it was not a census study, and the sample selection was not random but was affected by the student information available. This may hide important information from those who did not respond to the mathematical self-concept questionnaire, although the results about the relationship between performance and the online training were from the full cohort in [ 8 ], and the difference in terms of average performance is less than .4 points in the score (statistically significant), favorable to those in the subsample considered here. Additionally, since it was not a randomized controlled trial, results, even when being relevant, cannot be generalized to all the Colombian university population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the limitations of the study, it is worth noting that despite the large sample size, it was not a census study, and the sample selection was not random but was affected by the student information available. This may hide important information from those who did not respond to the mathematical self-concept questionnaire, although the results about the relationship between performance and the online training were from the full cohort in [ 8 ], and the difference in terms of average performance is less than .4 points in the score (statistically significant), favorable to those in the subsample considered here. Additionally, since it was not a randomized controlled trial, results, even when being relevant, cannot be generalized to all the Colombian university population.…”
Section: Discussionmentioning
confidence: 99%
“…Based on Khan Academy's facilities, students had access to videos, interactive exercises, and instant feedback that allowed them to reinforce their prior learning in mathematics individually and at their own pace. A previous study [ 8 ] found the effectiveness of this online training in terms of mathematical learning, with the active support of teachers. With the present study, the aim was to go further, identifying the various factors that could affect academic performance, opting for a social, technological, and personal perspective to examine the students' perceptions of their mathematical skills.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations